Diseño y construcción de banco de pruebas para puesta a punto de alternadores y bombas de vacío de vehículos isuzu para la empresa gmovil S.A.S - Aguirre Rodriguez, Oscar Andres (Universidad Antonio Nariño, 2021)
In this project the design of and construction of a test workbench for alternators and vacuum pumps of Isuzu vehicles for the company Gmovil SAS was made with the purpose of carrying out tests and diagnoses before and after the repairs of these elements and of This way, optimizing the quality control of the interventions on them. This is complemented by the analysis of the parameters where it is possible to generate load to the alternator, in order to corroborate the correct operation of the same in its electrical part, but additionally to have the possibility of validating the condition of the vacuum pump and the tightness of the hydraulic system. The most representative drawback is that the only way to prove them was when they were already installed in the vehicle, therefore when the faults were identified, either by the electrical part or by oil leaks, important repair logistics have already been advanced transportation, and installation labor to be reprocessed. As a response to this need, a workbench is manufactured that allows varying parameters such as revolutions of rotation, electrical load and oil pressure, additionally it allows measuring and displaying the variables necessary for diagnosis such as voltage and amperage, complemented with the option of observing the condition of the rectifier bridge by means of the oscilloscope.